Reservoir space and fractal characteristics of low-maturity shale in Dongying Sag: A case study of Upper Submember of Fourth Member in Eocene Shahejie Formation in Minfeng area - WANG Weiqing; WANG Xuejun; LI Zheng; WANG Yuhuan; ZHU Lipeng; LI Pengbo (Youqi dizhi yu caishoulu)
Low-maturity shale is widely distributed in Dongying Sag， which has abundant shale oil resources. However， the reservoir space and fractal characteristics of low-maturity shale reservoirs are not clear， which restricts the efficient development of low-maturity shale oil. In this paper， the low-maturity shale in the Upper Submember of the Fourth Member in the Eocene Shahejie Formation （Es4u） in Minfeng area of Dongying Sag was taken as the research object. The reservoir space types and the influence of lamina combinations on the reservoir space were discussed based on integrating core observation， slice analysis， organic geochemical test， X-ray diffraction， low-temperature nitrogen adsorption， and scanning electron microscopy， and the pore fractal characteristics were studied. The main lithofacies of the low-maturity shale of Es4u in the research area are organic-rich laminated calcareous mixed shale and organic-rich laminated argillaceous mixed shale. The pores of the organic-rich laminated calcareous mixed shale are mainly mesoporous and macroporous， and those of the organic-rich laminated argillaceous mixed shale are mainly microporous， with some macropores also being developed. The predominant reservoir space in the low-maturity shales are intergranular pores， interlamellar pores in clay minerals， and micro-fractures. Two laminae combinations， “micrite calcite laminae + argillaceous laminae” and “sparry calcite laminae + argillaceous laminae”， are widely developed in the study area. The micrite calcite laminae and sparry calcite laminae are dominated by intergranular pores， while argillaceous laminae are dominated by interlamellar pores in clay minerals. The interlamellar fractures and intergranular pores are important reservoir spaces for shale oil. The fractal dimension D1 of low-maturity laminaceous shale ranges from 2.413 9 to 2.527 7， and D2 ranges from 2.704 6 to 2.802 1. TOC content and carbonate mineral content are weakly negatively correlated with D1 and D2， while clay mineral contents are weakly positively correlated with D1. The intergranular pores and dissolution pores of carbonate minerals have smooth surfaces and simple pore space， which is conducive to shale oil accumulation and flow.